Injectable polymeric biomaterials: a brief review. (16th October 2015) - Dou, Jinbo; Sprague, Charles H.; Chen, Liang; Wang, Zaiqin; Wang, Shanfeng
Abstract : This review summarizes some recent work done by the corresponding author and his co-workers on photo-crosslinkable and injectable polymeric systems developed for biomedical applications. First, we discuss the synthesis, chemical structures, and physical properties of different injectable polymeric systems, including poly(propylene fumarate)-based, poly(ε-caprolactone)-based, and poly(ethylene glycol)-based homo-polymers, their copolymers and blends, and their nanocomposites containing hydroxyapatite (HA) nanoparticles or polyhedral oligomeric silsesquioxane nanocages. Then we present different fabrication methods of two-dimensional (2D) surface features, for example, honey-comb pores and microgrooves, and three-dimensional (3D) porous scaffolds and nerve conduits using these injectable polymeric systems. At last, we elaborate on the applications of these injectable polymeric systems, including regulation of in vitro cellular behavior on 2D substrates and 3D structures, and in vivo animal implantation of porous scaffolds and nerve conduits aiming for assisting bone regeneration and peripheral nerve regeneration, respectively.